Environmental Friendly Energy Sources in Cyprus - Kalogirou, Soteris A. (My University, 2006)
Cyprus has a small isolated energy system, almost totally dependent on imported fuels to meet its energy demand. The abundance of solar radiation, together with a good technological base, created favourable conditions for the exploitation of solar energy in the island. The contribution of solar energy to the total energy consumption is 4.5%. This energy is used mainly in the domestic sector (93.5%) for hot water production. Cyprus began manufacturing solar water heaters in the early sixties. The number of units in operation today corresponds to one heater for every 3.7 people in the island, which is a world record. Simulation studies and economic analysis of domestic systems show that 80% of the annual hot water needs of a house of four are covered while the life cycle savings of such system for the current rate of electricity are £740 (€1260) and the pay back time is 4 years. Additionally, such a system, saves 80% of the greenhouse gasses emissions compared to a conventional system. The prospects of the solar water heating industry are good. A sector that may be improved is that of the hotel industry. Additionally the use of solar energy for space heating and cooling and for process heat in industry is a further challenge for the Cyprus water heating industry. The use of other forms of renewable energy systems like PV and wind is very limited. This however is expected to change in the near future due to the incentives given by the Government with the new subsidisation scheme, which is in action since last year.
Keywords: Environmental friendly; Energy sources; Cyprus